Substantial Improvement of Operating Stability by Strengthening Metal‐Halogen Bonds in Halide Perovskites. (25th February 2022) - Chen, Xi; Sun, Zhiguo; Cai, Bo; Li, Xiaoming; Zhang, Shihua; Fu, Di; Zou, Yousheng; Fan, Zhiyong; Zeng, Haibo
Abstract: Solution‐processed lead halide perovskites (LHPs) hold great promise for low‐cost high‐performance solar cells and light‐emitting devices, but they also suffer from a serious operating instability problem due to the ionic migration and lattice decomposition driven by strong electric fields. Here, considerably suppressed ionic migration and enhanced lattice stability in LHPs with partial substitution of Pb with 3d transition metal (TM: Mn and Ni) are reported. It is experimentally shown that the energy barrier for ionic migration in CsPbBr3 can be increased fourfold by Mn and Ni substitution, even with a small doping level (< 4%). However, post‐TM Zn and non‐TM Bi incorporations are less efficient in suppressing ionic migration. The theoretical results reveal that Ni and Mn ions with partially filled 3d orbitals can passivate the active lone‐pair electron of surrounding Pb‐Br octahedrons via a coordination effect and reduce the Pb 6s‐Br 4p antibonding states, resulting in long‐range lattice stabilization and suppressed ionic migration. The Ni incorporation strategy in mixed‐halogen CsPbBr1.5 I1.5 is further demonstrated, for which the field‐driven halogen segregation is significantly mitigated and the associated emission color variation is reduced sixfold. This study paves the way for improving the operating stability in LHP‐based optoelectronic and electronic devices. Abstract : Transition metals with partially filled 3d orbitals such as Ni and Mn are incorporated into CsPbBr3 and CsPbBr1.5 I1.5 perovskites to passivate the lone‐pair electrons in Pb 6s‐halogen p antibonding states via a coordination effect, which enhances the metal‐halogen bond strength and consequently leads to a fourfold increase in the ionic migration energy barrier and sixfold reduction in emission color variation.